2020
DOI: 10.3389/fimmu.2020.00353
|View full text |Cite
|
Sign up to set email alerts
|

LXR Activation Induces a Proinflammatory Trained Innate Immunity-Phenotype in Human Monocytes

Abstract: Objectives: The concept of trained innate immunity describes a long-term proinflammatory memory in innate immune cells. Trained innate immunity is regulated through reprogramming of cellular metabolic pathways including cholesterol and fatty acid synthesis. Here, we have analyzed the role of Liver X Receptor (LXR), a key regulator of cholesterol and fatty acid homeostasis, in trained innate immunity. Methods and Results: Human monocytes were isolated and incubated with different stimuli for 24 h, including LXR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 39 publications
3
48
1
Order By: Relevance
“…Recently, it has also been shown that the liver X receptor (LXR), a key regulator of cholesterol and fatty acid homeostasis, may play a role in the establishment of innate memory ( 48 ). Human monocytes primed in vitro with LXR agonists and challenged after 5 days with a TLR2 agonist, Pam3Cys, showed an inflammatory activation accompanied by epigenetic reprogramming (increased H3K27ac and H3K4me3 on IL-6 and TNF-α promoters) and metabolic reprogramming (increased lactate production and decreased oxygen consumption) with respect to unprimed cells.…”
Section: Innate Memory and Metabolic Reprogrammingmentioning
confidence: 99%
“…Recently, it has also been shown that the liver X receptor (LXR), a key regulator of cholesterol and fatty acid homeostasis, may play a role in the establishment of innate memory ( 48 ). Human monocytes primed in vitro with LXR agonists and challenged after 5 days with a TLR2 agonist, Pam3Cys, showed an inflammatory activation accompanied by epigenetic reprogramming (increased H3K27ac and H3K4me3 on IL-6 and TNF-α promoters) and metabolic reprogramming (increased lactate production and decreased oxygen consumption) with respect to unprimed cells.…”
Section: Innate Memory and Metabolic Reprogrammingmentioning
confidence: 99%
“…This is important since a number of differences in LXR biology have been reported between human and rodent models, including the aforementioned species-specific regulation of certain genes 18,20,28,35 . Furthermore, in stark contrast to the anti-inflammatory effects of LXR activation in murine macrophages [36][37][38] , LXR has repeatedly been shown to potentiate pro-inflammatory responses in human monocytes 35,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…LXR activation can be pro-or anti-inflammatory depending on the timing of stimulation and species studied 35,39,40 . LXR activation has previously been reported to inhibit cytokine production by T cells 31,55,56 , generally attributed to repression of cytokine mRNA transcription 31,55 .…”
Section: Discussionmentioning
confidence: 99%
“…While apoptotic-cell derived ornithine and putrescine participates in "continual" efferocytosis and the anti-inflammatory program of human pro-resolving macrophages (10). LXR activation leads to anti-inflammatory functions [with upregulation of efferocytic receptor Tgm2 (37) and inhibition of TLR4 signaling (38)] and pro-inflammatory functions (15,16,38) [with the production of IL-1b via HIF-1a (15), as well as ROS (38)]. Human cells are less receptive to inosine and adenosine with reduced expression and function of adenosine receptors in comparison to mouse cells (39).…”
Section: Liver X Receptor Signaling Another Pathway Differing Betweementioning
confidence: 99%
“…The tissue microenvironment affects this antiinflammatory program of mouse macrophages residing in cavities by inducing the apoptotic cell recognition receptor, TIM-4, and down-regulating Toll-like receptor (TLR) 9 (14). Based on 3 recently published manuscripts (10,15,16) that bring significant contributions to human macrophage characterization and shed light on discrepancies between mouse and human resolving macrophages, we here comment and discuss this interspecies variability. Today, while mouse pro-resolving macrophages and the efferocytosis process begin to be deciphered, data on human macrophages remain scarce.…”
Section: Introductionmentioning
confidence: 96%